An All‐Organic Self‐Powered Photodetector with Ultraflexible Dual‐Polarity Output for Biosignal Detection (Adv. Mater. 30/2022). Issue 30 (27th July 2022) - Yan, Tingting; Li, Ziqing; Cao, Fa; Chen, Jiaxin; Wu, Limin; Fang, Xiaosheng
Abstract : Photodetectors Endowing photodetectors with mechanical flexibility and actual functionality are current research issues in developing optoelectronic devices. In article number 2201303, Xiaosheng Fang and co‐workers report an all‐organic self‐powered photodetector prepared by an all‐solution method with ultraflexible dual‐polarity output, which can be utilized in detecting steady biosignals for photo‐plethysmography application.